Agent-Based Simulation of Socially-Inspired Model of Resistance against Unpopular Norms - Zia, Kashif; Saini, Dinesh Kumar; Muhammad, Arshad; Farooq, Umar (Informatica, 2019)
People live in a society adhering to different types of norms, and some of these norms are unpopular. This paper proposes an agent-based model for unpopular norm aversion. The proposed model is simulated asking important “what-if” questions to elaborate on the conditions and reasons behind the emergence, spreading and aversion of unpopular norms. Such conditions can thus be analyzed and mapped onto the behavioral progression of real people and patterns of their interactions to achieve improved societal traits particularly using the new social landscape dominated by digital content and social networking. Hence, it can be argued that careful amalgamation of social media content can not only educate the people but also help them in an aversion of undesirable behaviors such as retention and spreading of unpopular norms. Simulation results revealed that to achieve a dominant norm aversion, an agent population must incorporate a rational model, besides, active participation of agents in averting unpopular norms.